Day 3 Wed, November 14, 2018 2018
DOI: 10.2118/192943-ms
|View full text |Cite
|
Sign up to set email alerts
|

Influence of EOR Polymers on Fouling in Production Wells and Facilities

Abstract: Cairn Oil & Gas, Vedanta Limited has implemented full field Polymer Flooding in Mangala Field and is currently injecting nearly 400,000 bpd of polymerized injection water with average polymer concentration of ~2500 ppm. Partially hydrolysed polyacrylamide (HPAM) Polymer is mixed with source water to create a mother solution of 15,000 ppm concentration at Central Polymer Facility (CPF) and is distributed through a pipeline network to 15 well pads where it is diluted to achieve a viscosity of ~30 cP for inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 1 publication
1
1
0
1
Order By: Relevance
“…As can be seen from Fig. 4, at the same polymer concentration, the deposit rate generally increases with the skin temperature but is much more pronounced between 165 F and 250 F (i.e., the curve slope between 165 F and 250 F) than between 250 F and 350 F. This phenomenon confirms that skin temperature is one of the critical factors affecting the fouling tendency on the heating tube surface, which is consistent with previous studies (Shupe 1981;Ramsden and McKay 1986;Moradi-Araghi and Doe 1987;Seright and Skjevrak 2015;Xiong et al 2018). That is because the temperature can significantly affect the degree of hydrolysis of polyacrylamide in the solution (Muller et al 1980 With the increase in temperature, the degree of hydrolysis can be significantly higher than 30%.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As can be seen from Fig. 4, at the same polymer concentration, the deposit rate generally increases with the skin temperature but is much more pronounced between 165 F and 250 F (i.e., the curve slope between 165 F and 250 F) than between 250 F and 350 F. This phenomenon confirms that skin temperature is one of the critical factors affecting the fouling tendency on the heating tube surface, which is consistent with previous studies (Shupe 1981;Ramsden and McKay 1986;Moradi-Araghi and Doe 1987;Seright and Skjevrak 2015;Xiong et al 2018). That is because the temperature can significantly affect the degree of hydrolysis of polyacrylamide in the solution (Muller et al 1980 With the increase in temperature, the degree of hydrolysis can be significantly higher than 30%.…”
Section: Resultssupporting
confidence: 90%
“…Even the used chemicals may react with the minerals aggravating the mineral fouling issues. Previously, the study of Moradi-Araghi and Doe (1987) demonstrated that hydrolyzed polyacrylamides (HPAM) could precipitate when hard brines were present, especially under high-temperature conditions (greater than the cloud point), because the calcium ions could bind with the polymer caused by reacting or crosslinking with the acrylic group of HPAM. Recently, studies have been conducted to investigate the fouling issues in production systems of chemical EOR projects.…”
Section: Introductionmentioning
confidence: 99%
“…После того как он подтвердил эффективность началось наращивание количества скважин под закачку полимерного раствора (рис. 11) [32].…”
Section: рисунок 9 пилотный участок на месторождении Matzenunclassified